A market-based solution to a sanitation issue in a marginalised area. Issue 6 (18th August 2018) - Yadav, Vikash
ABSTRACT: Neo-liberal ideology, as an abstract technique of self-governance and population management, is often viewed as tolerant of extreme inequality within a market economy. However, the range of policy proposals that flow from the ideology are not necessarily insensitive to development projects in marginalised areas. Sensitivity to market mechanisms may inject pragmatism in contexts where states are unable or unwilling to supply capability enhancing public goods. Through an analysis of the Center for Urban and Regional Excellence's proof-of-concept development project in India, this article argues that a market-oriented framework can be useful in mitigating collective action problems.